2017
DOI: 10.1002/jcp.25871
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue engineering with micronized‐gingival connective tissues

Abstract: The free gingival graft (FGG) and connective tissue graft (CTG) are currently considered to be the gold standards for keratinized gingival tissue reconstruction and augmentation. However, these procedures have some disadvantages in harvesting large grafts, such as donor‐site morbidity as well as insufficient gingival width and thickness at the recipient site post‐treatment. To solve these problems, we focused on an alternative strategy using micronized tissue transplantation (micro‐graft). In this study, we fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Trovato et al (2015) [ 9 ] have shown that the obtained tissue solution is rich in progenitor cells for tissue regeneration. Regarding the wound healing study, an animal study using gingival connective tissue has been recently reported [ 10 ]. Moreover, clinical trials using the technique have also been performed, such as dehiscent surgical wounds [ 11 ], complex wound [ 12 ], chronic ulcers [ 13 ] and chronic scars [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trovato et al (2015) [ 9 ] have shown that the obtained tissue solution is rich in progenitor cells for tissue regeneration. Regarding the wound healing study, an animal study using gingival connective tissue has been recently reported [ 10 ]. Moreover, clinical trials using the technique have also been performed, such as dehiscent surgical wounds [ 11 ], complex wound [ 12 ], chronic ulcers [ 13 ] and chronic scars [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is already well known that oxidative stress is associated with the onset and progression of DN ( 28 ). The present study's result also added novel evidence to the role of oxidative stress by describing alterations in certain known functional processes or pathways, including flavonoid-associated processes ( 29 ), cytochrome P450 ( 30 ) and glutathione metabolism ( 31 ). Alterations in other DN-associated pathways ( 32 ), including the renin-angiotensin system, PPAR signaling pathway and arachidonic acid metabolism were also demonstrated in the present study.…”
Section: Discussionmentioning
confidence: 72%
“…This tissue graft was immediately processed into a dissociated soft-tissue suspension with 1 mL of 10% sucrose solution using a tissue dissociative device (Rigenera; Human Brain Wave, Italy, Fig. 1b) for 60 s [11].…”
Section: Preparation Of Dissociated Soft-tissue Suspensionmentioning
confidence: 99%
“…Recently, autologous micrograft, which is a dissociated cell suspension made out of tissue grafts, has received much attention as a promising material for soft-tissue engineering applications and plastic surgical procedures in the clinical setting [11]. Autologous micrograft (diameter < 50 μm) has been shown to facilitate improved wound healing [12] and hair transplantation [13], likely by ensuring the transplantation of an optimal cellular microenvironment and extracellular matrix, as well as of the target cells [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation